PENDAPATAN PADI SAWAH DENGAN TEKNOLOGI TABELA DAN TAPIN DI KELURAHAN UNAAHA KECAMATAN UNAAHA KABUPATEN KONAWE - Masrid Laguna (Yayasan Akrab Pekanbaru, 2019)
Improving the standard of living of farming communities can be achieved through sustainable agricultural development. Sustainable agricultural development is marked by the existence of sustainable production that provides benefits and the freedom for farmers to determine the best choice in farming. This study aims to find out how much farm income with the application of direct seed planting systems (Tabela) and transplanting (Tapin), find out how much the comparison of farm direct income planting systems (Tabela) and transplanting systems (Tapin) and find out whether farming systems direct seed planting (Tabela) and transplanting (Tapin), feasible or not. The location of the study was determined intentionally, the determination of respondents carried out by the census method the number of respondents in this study were 30 people with the division of 15 farmers who used the table system 15 farmers who used the tapin system. The results of this study are the average / ha income of rice farming in the transplanting system (Tapin) is greater than the average income / ha of rice farming in the direct seed planting system (Tabela).